FERTILIZERS AND MANURES - Renuka Sharma; Renuka Sharma (New Delhi Discovery)
The text book provides brief updated information about principles of soils, as they exists and interact in the environment with focus on fertilizer and Manure.
Fertilizer sector Manures in Drylands Manure Management
Keywords: Fertilizer sector, Manures in Drylands, Manure Management